2017
DOI: 10.1016/j.jsxm.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Investigation of the Micro-Organisms Involved in Penile Prosthesis Infection: An Analysis of the Efficacy of the AUA and EAU Guidelines for Penile Prosthesis Prophylaxis

Abstract: Introduction Penile prosthesis infections remain challenging despite advancements in surgical technique, device improvements, and adoption of antibiotic prophylaxis guidelines. Aim To investigate penile prosthesis infection microbiology to consider which changes in practice could decrease infection rates, to evaluate current antibiotic prophylaxis guidelines, and to develop a proposed algorithm for penile prosthesis infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 10 publications
2
69
0
4
Order By: Relevance
“… 19 In a retrospective multi-institutional study comprising 25 institutes, anaerobes, Candida and methicillin-resistant S aureus comprised nearly one third of positive cultures. 20 In this study, neither anaerobes nor Candida would have been isolated based on the incubation conditions, and S aureus was not detected.…”
Section: Discussionmentioning
confidence: 52%
“… 19 In a retrospective multi-institutional study comprising 25 institutes, anaerobes, Candida and methicillin-resistant S aureus comprised nearly one third of positive cultures. 20 In this study, neither anaerobes nor Candida would have been isolated based on the incubation conditions, and S aureus was not detected.…”
Section: Discussionmentioning
confidence: 52%
“…Among all the risk factors, the most important ones seem to be, without doubt, the presence of diabetes mellitus and the reintervention (defined as a change of penile prosthesis): in fact, while the incidence of infection after de novo implant is found only in 1–3% of the patients, in cases of revision surgery, the risk increases to 10% and in diabetic patients, it has even been reported to reach 18% [5]. Many of the selected articles addressed the prevention of PPI, but there is no clear consensus worldwide on certain topics, including the use of antibiotic therapy: about this topic, the 2 most relevant studies [6, 7] suggested that higher doses of gentamicin act as a protective factor; however, no significant association was found.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Gross et al [7, 8] also identifies the most implicated pathogens: they obtained 227 intraoperative cultures at salvage or explantation and identified 204 organisms and documented a high incidence of infections with Escherichia coli (18.3%), coagulase-negative Staphylococcus (15%), Candida species (11.1%), MSSA (10.5%), and MRSA (9.2%). Intravenous antibiotic regimens for all patients at implantation were generally, but not always, consistent with AUA or EAU guidelines: 22% (49 of 227) received a cephalosporin (cefazolin) and an aminoglycoside (gentamicin) and 56% (126 of 227) received vancomycin and an aminoglycoside (gentamicin) at implantation.…”
Section: Resultsmentioning
confidence: 99%
“…De prothese moet met spoed verwijderd worden. Dit risico ligt in de laatste series rond de 1,4-8,9 % [5][6][7]. Een laaggradige infectie wordt meestal veroorzaakt door de Staphylococcus epidermidis.…”
Section: Wat Zijn De Risico's?unclassified
“…Dan is de patiënt niet ziek en zichtbaar exsudaat is helder. Behandeling bestaat uit antibiotica en zo nodig een salvageprocedure [6,7]. Bij die procedure wordt de prothese in dezelfde setting vervangen.…”
Section: Wat Zijn De Risico's?unclassified